Studies of Co-Processed Hydrophilic Polymer Composites of Cissus Gum with Acacia, Tragacanth or Guar Gums: Processing and Characterization - Ugoeze, Kenneth Chinedu; Ameh, Bethel Covenant (European Journal of Applied Sciences, 2021)
New hydrophilic polymers were developed by co-processing of Cissus gum (CG) with acacia (AG), guar (GG) or tragacanth (TG) gums. Batches of new polymers were co-processed from the gum obtained from the stem of Cissus populnea (CG) with AG in the respective proportions of 5(%w/w)CG + 95(%w/w)AG, 10(%w/w)CG+90(%w/w)AG, 15(%w/w)CG +85(%w/w)AG and 20(%w/w)CG +80(%w/w)AG. Similarly to co-process polymers were developed with CG and TG or GG. A 50.0ml aqueous based slurry was made with each set of ingredients, precipitated with acetone, dried (desiccator), pulverized (180µm) and assessed for densities, flowabilty, moisture characteristics, pH and viscosities. The bulk and tapped densities varied statistically within the starting and the co-processed polymers (P<0.05), indicating that the co-processed powders may be compressible light bulk powders with low flowability due to high interparticulate interactions confirmed from the results of the flow rate, angle of repose, Carr’s index and Hausner’s ratio. Moisture contents of the staring materials appeared similar (P>0.05), but increased in the co-processed powders as CG+GG>CG+TG>CG+AG (P>0.05). Hydration capacity of the initial polymers ranked as CG>TG>GG>AG (P<0.05), increased with the increment of CG in the co-processed powders, as CG+TG>CG+GG>CG+AG (P<0.05). The swelling index of the initial materials presented as CG>GG>AG>TG (P<0.05), increased in the co-processed powders with increasing CG as CG+TG>CG+GG>CG+AG (P<0.05). The viscosities of the initial polymers ranked as GG>TG>CG>AG (P<0.05) and in the co-processed powders as CG+GG>CG+TG>CG+AG (P<0.05). Therefore, the study resulted in new co-processed hydrophilic polymers with improved hydration and swelling capabilities and viscosities advantageously essential in the adjuvants exploited as binders, disintegrants, emulsifiers, especially in the formulation of in-diffusible drugs in the liquid disperse systems necessitating the uniform and stable dispersion of the API coupled with enhanced viscosities and pH stability.